2007
DOI: 10.17660/actahortic.2007.735.22
|View full text |Cite
|
Sign up to set email alerts
|

Technique for Rapid Multiplication of Guava (Psidium Guajava L.)

Abstract: Wedge method of grafting was tried in guava (Psidium guajava L.) cultivars Allahabad Safeda and Sardar under greenhouse (GH) as well as in open field conditions (OFC) for 3 consecutive years (2003-2005). The grafting operation performed in greenhouse gave significantly (P=0.05) higher success of grafts (64.56-94.33%) as compared to open field conditions (51.30-78.63%) in both the cultivars. However, maximum success of grafts was obtained in greenhouse (88.63-94.33%) as well as in open field conditions (66.6-78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Guava (Psidium guajava L.) is one of the most promising fruit crops of India and is considered as one of the nutrionally valuable and remunerative crops (Singh et al, 2007). Guava fruits are used for both, fresh consumption and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Guava (Psidium guajava L.) is one of the most promising fruit crops of India and is considered as one of the nutrionally valuable and remunerative crops (Singh et al, 2007). Guava fruits are used for both, fresh consumption and processing.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the lowest graft survival (47.82 %, 44.66 % and 35.08 %) was registered in Lalit at 30, 60 and 90 days respectively after softwood grafting. Singh et al, (2007) also reported that significantly higher success of grafts (64.56-94.33%) in green house compared to open field condition (51.30-78.63%) in Sardar and Allahabad Safed (Fig. 1, 2 and 3).…”
Section: Graft Survivability (%)mentioning
confidence: 75%
“…Maximum plant height (cm) and length of scion shoot (cm) (64.95 and 39.05) respectively performed in March. Singh and Sengupta (1996) also recorded maximum sprout length in the plants grafted during March. The higher plant and scion length recorded in plants grafted in March and April in the present study may be because of the fact that grafted plant faced long periods of rainy season.…”
Section: Resultsmentioning
confidence: 94%